Arctic sea ice, 1973-1976 : satellite passive-microwave observations - Parkinson, Claire L; United States. National Aeronautics and Space Administration. Scientific and Technical Information Branch (Washington, DC : Scientific and Technical Information Branch, National Aeronautics and Space Administration, 1987)
Mode of access: Internet.